Política científica e tecnológica e patentes: o Proálcool - Uehara, Yaeko (2010)
This thesis aims to analyze the articulation and the relationship of public policies to encourage the scientific production in Brazil and the patent system in the period from the creation of the National Alcohol Program in 1980 until 2005. In this work there are two distinct periods: the intervention of the State, by means of centralized economic planning, and the period of deregulation, regulated by market laws. In this sense, this thesis focuses on the role of government as regulator and then enabling a policy of developing a local and exclusive renewable energy generation and the mutual relations between the different interests of social groups involved in this process. Also covers the history of science, technology and technical process of producing ethanol from sugarcane. Finally makes a mapping of patents granted to sugar cane and ethanol, as well as the final protections of the cultiving of sugarcane in the related period. The starting point was the assumption that the mapping of intellectual property granted in the period to sugarcane and ethanol in Brazil allows delineating the complex network interfaces of the various groups and institutions and their participation in development and consolidation of national science and technology. For this work the main government documents produced during the period, legislation and incentive mechanisms were analyzed. Simultaneously the records relating to patents from the database of the National Institute of Industrial Property were collected. From basic bibliography new developments concerning the relationship of science policy with patents and plant variety protection have been outlined